2020
DOI: 10.3389/fvets.2020.00582
|View full text |Cite
|
Sign up to set email alerts
|

Small and Large Animal Veterinarian Perceptions of Antimicrobial Use Metrics for Hospital-Based Stewardship in the United States

Abstract: Background: Robust measurement and tracking of antimicrobial use (AMU) is a fundamental component of stewardship interventions. Feeding back AMU metrics to individual clinicians is a common approach to changing prescribing behavior. Metrics must be meaningful and comprehensible to clinicians. Little is known about how veterinary clinicians working in the United States (US) hospital setting think about AMU metrics for antimicrobial stewardship. Objective: To identify hospital-based veterinary clinicians' attitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
(91 reference statements)
1
6
0
Order By: Relevance
“…In the current study, more than half of the respondents use domestic or foreign guidelines moderately when prescribing antibiotics in their daily work; however, almost all of them would also like to have more local guidelines available. Other studies conducted in the USA have had similar results [ 74 , 75 ].…”
Section: Discussionsupporting
confidence: 75%
“…In the current study, more than half of the respondents use domestic or foreign guidelines moderately when prescribing antibiotics in their daily work; however, almost all of them would also like to have more local guidelines available. Other studies conducted in the USA have had similar results [ 74 , 75 ].…”
Section: Discussionsupporting
confidence: 75%
“…Interactive meetings and discussions with other veterinarians and course organizers, as well as individual, clinic-based feedback, were highly appreciated. Participants from the former ASAP project reported that they were interested in seeing how their prescribing compared to other veterinarians (benchmarking), which is also underlined by other studies [42]. Having interactive discussions with other participants and course organizers might deepen insight and motivate participants to consider alternative attitudes.…”
Section: Discussionmentioning
confidence: 96%
“…While there are some nuances across metrics which might relate to different stewardship program priorities, the differences are slight with the exception of measuring mass-based grams compared to a dose-based measure of treatment incidence ( 14 16 ). In a study looking at benchmarking both large and small animal clinicians in the United States it was found that “Prescribing frequency, durations of therapy, and ranking of antimicrobial classes appear to be the metrics most well-received by veterinary clinicians, while dose-based metrics associated with the ADD [animal daily dose] are less intuitive.” ( 17 ); even in a hospital setting with clinicians interpreting the benchmarks, dose-based metrics were perceived as “less intuitive.”…”
Section: Discussionmentioning
confidence: 99%